Vapour-liquid-liquid equilibria measurements for the dehydration of low molecular weight alcohols via heterogeneous azeotropic distillation - Brits, Leanne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.